Effects of Conventional and Organic Agriculture on Soil Arbuscular Mycorrhizal Fungal Community in Low-Quality Farmland - Chen, Jiawei; Li, Jianwei; Yang, Yurong; Wang, Yimei; Zhang, Yifei; Wang, Ping (Frontiers in Microbiology, 2022)
Arbuscular mycorrhizal (AM) fungi have promising applications in low-quality farmlands all over the world, but research on their responses to conventional and organic farming systems in low-quality soil is limited. We hypothesized that the colonization activity and community diversity of AM fungi in conventional farming systems may not be lower than in organic farming on low-quality farmlands where beneficial symbiosis is required. We collected soil and maize root samples from medium to low fertility farmlands with conventional or organic farming systems in western Jilin Province, China. The colonization percentage and intensity, taxonomic and phylogenetic diversity, community composition of soil AM fungi, and soil factors were detected and compared between the two farming systems. The colonization intensity and operational taxonomic unit (OTU) taxonomic diversity on conventional farms were higher than on organic farms. Glomus was the most common genus on conventional farms, whereas Paraglomus and Glomus were the most common on organic farms. We also found a simpler AM fungal network structure with lower OTU phylogenetic diversity on conventional farms. Our findings suggested that though the conventional farming system resulted in different compositions and simpler structures of soil AM fungal community, there are potential diverse OTU resources currently present on conventional farms. This work has potential impacts on understanding the influence of different farming systems on soil AM fungi in low-quality farmlands and the development of efficient mycorrhizal inoculant production.